Changing Literacies and Civic Pathways: Multiliteracies in Inquiry-Driven Classrooms. Issue 1 (2nd January 2018) - Seglem, Robyn; Garcia, Antero
Abstract : Reflecting on how "the very nature of language learning has changed"(New London Group [NLG], 1996, p. 64), this article describes an inquiry-driven teaching approach to middle school English. Looking at student outcomes utilizing Google's 20% approach, this study explored how mentorship, digital tools, and student interests provide "opportunities [for students] to find their own voices" (NLG, 1996, p. 71). In particular, this article analyzes student inquiry based on the 4 pedagogical foundations of multiliteracies: situated practice, overt instruction, critical framing, and transformed practice. By focusing on the voices and experiences of students, this framework highlights what multiliteracies can look like within classrooms. Ultimately, this study of literacies within inquiry-driven classrooms responds to the call of multiliteracies research from 20 years ago that, "Students need to develop the capacity to speak up, to negotiate, and to be able to engage critically with the conditions of their working lives" (New London Group, 1996, p. 67).